2021
DOI: 10.3389/fonc.2021.632352
|View full text |Cite
|
Sign up to set email alerts
|

Long Distance From Microvessel to Cancer Cell Predicts Poor Prognosis in Non-Small Cell Lung Cancer Patients

Abstract: BackgroundBlood supply, which is crucial for nutrition and drug delivery, was determined by microvessel density as well as the diffusion distance between vessels and cancer cells. Therefore, we evaluated the distance from microvessels to cancer cells (Dmvcc) and its role in the prognosis of non-small cell lung cancer (NSCLC) patients.MethodsPatients with primary NSCLC were retrospectively analyzed. The tumor samples were immunochemically stained with CD31 to visualize the microvessels. The Dmvcc was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Sustained angiogenesis is considered to be an important hallmark of NSCLC [ 32 ]. Angiogenesis contributes to NSCLC development by providing oxygen and nutrients and facilitating tumor growth and metastasis [ 33 ]. We found that the tumor angiogenesis was predominantly featured by tip cell infiltration-the main cells at the tips of vascular sprouts integrating multiple activities during angiogenesis [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sustained angiogenesis is considered to be an important hallmark of NSCLC [ 32 ]. Angiogenesis contributes to NSCLC development by providing oxygen and nutrients and facilitating tumor growth and metastasis [ 33 ]. We found that the tumor angiogenesis was predominantly featured by tip cell infiltration-the main cells at the tips of vascular sprouts integrating multiple activities during angiogenesis [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%